Sustainable Spending in Destinations : Factors Discouraging Tourists - Ravichandran, Sabari Shankar; Koshy, Elizabeth Renju; Natarajan, Subhashree (Indian Journal of Finance, 2024)
Purpose : This study investigated the factors influencing tourists’ sustainable spending behavior in tourism destinations aimed to provide insights for policymakers and businesses to promote sustainability. The research objectives included identifying key factors affecting sustainable spending, assessing their impact, and examining their implications. Methodology : A quantitative approach utilizing confirmatory factor analysis (CFA) was employed to analyze data collected from tourists visiting destinations. Findings : The major findings revealed six significant factors: Perceived costs, availability, awareness, convenience, hedonism & benefits, and culture, elucidating the complex interplay shaping sustainable spending behavior. Theoretical Implications : The importance of perceptions, awareness, and cultural norms in understanding tourists’ spending decisions has been found to be value added to the literature. A comprehensive measurement technique has been produced in the literature. Practical Implications : This study offered insights for marketers to address perceived cost concerns, enhance availability, and promote awareness of sustainable options. Policymakers could use these findings to formulate targeted policies and incentives to encourage sustainable spending. This research also contributed to advancing the understanding of sustainable tourism spending and provided actionable insights to promote sustainability in line with the United Nations Sustainable Development Goals (UNSDGs).